Implementation of Pre-Trial Legal Efforts Taken by Suspects of Crimes of Sexual Abuse Against Minors - Jati, Fajar Nur Hafiz; Hartono, Bambang; Ansori, Ansori (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Law is a means of punishment, where a criminal act is an act that is prohibited by a rule of law, where the prohibition is accompanied by a threat (sanction) in the form of a certain form of punishment. Problems in law enforcement that often occurred from the Dutch colonial era until after independence were related to coercive efforts carried out by law enforcement officials, especially investigators and public prosecutors. Pre-trial is an institution organized to examine coercive actions carried out by authorized officials as law enforcers. The idea of a Pre-Judicial institution was born from inspiration originating from the existence of the right of Habeas Corpus in the Anglo Saxon justice system, which provides fundamental guarantees for human rights, especially the right to liberty. The Habeas Corpus Act gives a person the right, through a court order, to sue (challenge) officials who implement formal criminal law (police or prosecutors) so that they do not violate the law (illegally) or, strictly speaking, are truly legal in accordance with applicable legal provisions. The issues that will be discussed in this writing are, the process of investigating alleged criminal acts of sexual abuse against minors at the Tulang Bawang Police Criminal Investigation Unit and the Judge's Considerations in deciding the Pre-Trial application from the applicant's application in Decision Number: 3/Pid.Pra/2022/PN. Mgl. The research method used is a normative juridical and empirical approach, using secondary and primary data, obtained from literature studies and field studies, and data analysis using normative juridical analysis. The results of research regarding the process of investigating alleged criminal acts of sexual abuse against minors are investigations that require a process such as making a report, carrying out an investigation, checking the post mortem, carrying out the case title, then sending a letter notifying the start of the investigation which aims to notify about the conduct of an investigation into a case, carry out investigations into statements from witnesses, determine suspects, conduct examinations of suspects, collect evidence, and carry out filings. The end of the investigation process which is the investigator's task is marked by a complete investigation report (P-21) or commonly called with Stage 1 and handing over evidence and also the suspect to the public prosecutor (P-22) or called Stage 2. Then the judge's consideration in giving a decision on a fraud case is the presence of evidence to prove which party is wrong and right, then the presence of witnesses who was presented at the trial to explain the chronology of the incident. Because of this, the judge decided to reject the Petitioner's pretrial application in its entirety, charging the Petitioner court costs of nil. The suggestion is that it is hoped that in the future the Tulang Bawang Police will play an active role in preventing or eradicating cases of sexual abuse against minors and other cases of sexual crimes in Tulang Bawang Regency. The public is also expected to immediately report any crime so that the investigation process can proceed well.